2017
DOI: 10.1136/bcr-2017-220768
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae-induced rash and mucositis: a recently described entity

Abstract: Mycoplasmapneumoniaeis a common cause of respiratory infections. Although most cases are mild, some patients have extrapulmonary complications including mucocutaneous eruptions including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and erythemamultiforme (EM). Recently, a new entity, calledM. pneumoniae-induced rash and mucositis (MIRM) was described. The authors present a clinical case difficult to classify attending to the classical classification of epidermolytic syndromes that meets the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
(18 reference statements)
0
24
0
3
Order By: Relevance
“…In the literature, we find terms such as "incomplete SJS", "SJS without skin lesions", "atypical SJS" or recently "Fuchs syndrome", "M. pneumoniae-associated mucositis (MPAM)" and "M. pneumoniae-induced rash and mucositis (MIRM) sine rash" to describe patients who, in the context of an MP infection, develop extensive mucositis consistent with SJS, but with minimal or no cutaneous involvement [1,2,[4][5][6][7][8][9][10][11]. Whether MPAM should be considered a separate entity from SJS or it belongs in the same spectrum is still debated [1,2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, we find terms such as "incomplete SJS", "SJS without skin lesions", "atypical SJS" or recently "Fuchs syndrome", "M. pneumoniae-associated mucositis (MPAM)" and "M. pneumoniae-induced rash and mucositis (MIRM) sine rash" to describe patients who, in the context of an MP infection, develop extensive mucositis consistent with SJS, but with minimal or no cutaneous involvement [1,2,[4][5][6][7][8][9][10][11]. Whether MPAM should be considered a separate entity from SJS or it belongs in the same spectrum is still debated [1,2,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…MPAM usually develops in young males (< 18 years), presenting prodromes during the previous week with coughing, fever and general discomfort [1,2,[4][5][6][7][8][9][10][11]. Mucosal involvement is intense and fundamental for the diagnosis, with oral involvement most frequent (94-100 %, with erosions or denudation of the entire mucosa), followed by conjunctival involvement (82-97 %, with bilateral conjunctivitis) and urogenital involvement (63-78 %, with ulcerations and vesiculobullous lesions) [1,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 25% of cases there are extrapulmonary complications, namely mucocutaneous lesions [15] . The MP spectrum of dermatological manifestations is varied and includes Raynaud’s disease, erythema nodosum, Kawasaki disease, erythema multiforme (EM) and Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) [25]. Mucositis with or without scarce cutaneous involvement associated with MP infection is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Mucositis with or without scarce cutaneous involvement associated with MP infection is rare. Previously this clinical condition was classified within the epidermolytic dermopathy spectrum, being classified as ‘atypical SSJ’, ‘incomplete SSJ’ or ‘Fuchs syndrome’ [1,2,4] . A recent systematic review concluded that this condition is actually a distinct entity called Mycoplasma pneumoniae -induced rash and mucositis (MIRM) [1] .…”
Section: Discussionmentioning
confidence: 99%